2008
DOI: 10.1007/s10535-008-0073-9
|View full text |Cite
|
Sign up to set email alerts
|

Direct organogenesis from leaf explants of Stevia rebaudiana and cultivation in bioreactor

Abstract: Shoot buds were induced directly on either side of midrib from adaxial surface of immature leaf explants in Stevia rebaudiana Bertoni five weeks after culturing in Murashige and Skoog's nutrient medium supplemented with 8.88 μM of N 6 -benzylaminopurine and kinetin ranging from 4.65 to 6.98 μM. Immature leaves of 0.6 to 1 cm were found to produce best response (93 %) with a highest number of 4.93 shoot buds per explant. For elongation of regenerated shoot buds, MS medium supplemented with 30 g dm -3 sucrose an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
42
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(50 citation statements)
references
References 14 publications
7
42
0
1
Order By: Relevance
“…SILVA et al (2007) working with different methods of pineapple propagation, reported a bigger length of the aerial part with the use of temporary immersion bioreactor, being superior to other methods like continuous immersion bioreactor and conventional micropropagation. Similar results have been found in chrysanthemums ; apples (CHAKRABARTY et al, 2007), in the medicinal plants Crescentia cujete (MURCH et al, 2004) and Stevia rebaudiana (SREEDHAR et al, 2008). MURCH et al (2004), working with different Crescentia cujete growth systems, reported that a bigger growth of the root system was observed in temporary immersion system when compared to the micropropagation in solid and liquid media.…”
Section: ---------------Rsl (Cm) --------------------------------Pfm(supporting
confidence: 78%
“…SILVA et al (2007) working with different methods of pineapple propagation, reported a bigger length of the aerial part with the use of temporary immersion bioreactor, being superior to other methods like continuous immersion bioreactor and conventional micropropagation. Similar results have been found in chrysanthemums ; apples (CHAKRABARTY et al, 2007), in the medicinal plants Crescentia cujete (MURCH et al, 2004) and Stevia rebaudiana (SREEDHAR et al, 2008). MURCH et al (2004), working with different Crescentia cujete growth systems, reported that a bigger growth of the root system was observed in temporary immersion system when compared to the micropropagation in solid and liquid media.…”
Section: ---------------Rsl (Cm) --------------------------------Pfm(supporting
confidence: 78%
“…Initially, the shoot buds appeared as white knob like structures which later turned green leading to the formation of a pair of green leaves (Sreedhar et al, 2008). In an earlier study, kin in combination with NAA or IAA failed to induce shoot formation on leaf explants of stevia whereas BA was found to be more effective (Sivaram and Mukundan, 2003).…”
Section: Establishment Of In Vitro Culture Of Stevia Through Leaf Expmentioning
confidence: 94%
“…These vein-derived cells are procambial-like and function as pluripotent stem cells with a tendency to form root meristems or vascular tissues in response to added auxin (Rose et al, 2006). A series of experiments with Cyclamen persicum led to the conclusion that an increased density of vascular tissue will increase root regeneration as a result of the level of phytochromes and other metabolites that are present in the leaf midvein (Sreedhar et al, 2008). Furthermore, the ability of leaf explants in producing its endogenous auxins might also contribute to the more effective adventitious root formation from the leaf than that of stem explants which lack this ability (Vesperinas, 1998).…”
Section: Root Induction From In Vitro Leaf and Stem Explantsmentioning
confidence: 99%